Differentiation in the protein synthesis-dependency of persistent synaptic plasticity in mossy fiber and associational/commissural CA3 synapses in vivo - Hardy eHagena; Denise eManahan-Vaughan (Frontiers in Integrative Neuroscience, 2013)
Long-term potentiation (LTP) and long-term depression (LTD) are two mechanisms involved in the long-term storage of information in hippocampal synapses. In the hippocampal CA1 region, the late phases of LTP and LTD are protein-synthesis dependent. In the dentate gyrus, late-LTP but not LTD requires protein synthesis. The protein synthesis-dependency of persistent plasticity at CA3 synapses has not yet been characterized.Here, the roles of protein transcription and translation at mossy fiber (mf) and associational/commissural (AC)- synapses were studied in freely behaving rats. In control animals, low-frequency stimulation (LFS) evoked robust LTD (>24h), whereas high-frequency simulation (HFS) elicited robust LTP (>24h) at both mf-CA3 and AC-CA3 synapses. Translation inhibitors prevented early and late phases of LTP and LTD at mf–CA3 synapses. In contrast, at AC–CA3 synapses, translation inhibitors prevented intermediate/late-LTP and late-LTD only. Transcription effects were also synapse-specific: whereas transcription inhibitors inhibited late-LTP and late-LTD (>3h) at mf–CA3 synapses, at AC–CA3 synapses, protein transcription affected early-LTP and late-LTD. These results show that the AC-CA3 and mf-CA3 synapses display different properties in terms of their protein synthesis dependency, suggesting different roles in the processing of short- and long term synaptic plasticity.